Pengaruh Isometric Handgrip Exercise terhadap Tekanan Darah pada Lansia dengan Hipertensi di Desa Gringging Kabupaten Sragen - Opie Yunia Widiati; Riyani Wulandari (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Background: The prevalence of hypertension in Indonesia in 2021 reached 34.1% or more than 70 million people, and in Central Java in 2021 hypertension patients reached 37.57%. One of the interventions that supports is isometric handgrip exercise, to reduce blood pressure. Objective: To determine the effect of isometric handgrip exercise on blood pressure in elderly with hypertension in Gringging Village, Sragen Regency. Methods: The type of research is quantitative, the research method uses Pre-Exsperiment with One Group Pre Test-Post Test design. Using nonprobability sampling technique with purposive sampling method. Sampling as many as 15 respondents. The research instrument uses a sphygmomanometer. Data analysis with wilcoxon test. Results: in the study isometric handgrip exercise was given for 5 consecutive days with a time of 3 minutes and each hand got 2 contractions with a duration of 45 seconds per contraction. The results of the Wilcoxon test obtained a p-value of 0.000 <0.05. Conclusion: There is a significant effect of isometric handgrip exercise on blood pressure in elderly with hypertension in Gringging Village, Sragen Regency.